Medulloblastoma and ependymoma cells display levels of 5-carboxylcytosine and elevated TET1 expression - Ramsawhook, Ashley; Lewis, Lara; Coyle, Beth; Ruzov, Alexey (BioMed Central, 2017)
Background Alteration of DNA methylation (5-methylcytosine, 5mC) patterns represents one of the causes of tumorigenesis and cancer progression. Tet proteins can oxidize 5mC to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine and 5-carboxylcytosine (5caC). Although the roles of these oxidised forms of 5mC (oxi-mCs) in cancer pathogenesis are still largely unknown, there are indications that they may be involved in the mechanisms of malignant transformation. Thus, reduction of 5hmC content represents an epigenetic hallmark of human tumours and, according to our recent report; 5caC is enriched in a proportion of breast cancers and gliomas. Nevertheless, the distribution of oxi-mCs in paediatric brain tumours has not been assessed. Findings Here we analyse the global levels and spatial distribution of 5hmC and 5caC in 4 brain tumour cell lines derived from paediatric sonic hedgehog (SHH) pathway activated medulloblastomas (Daoy and UW228-3) and ependymomas (BXD-1425EPN and DKFZEP1NS). We show that, unlike HeLa cells, the paediatric tumour cell lines possess both 5hmC and 5caC at immunochemically detectable levels, and demonstrate that both modifications display high degrees of spatial overlap in the nuclei of medulloblastomas and ependymomas. Moreover, although 5hmC levels are comparable in the 4 brain tumour cell lines, 5caC staining intensities differ dramatically between them with highest levels of this mark in a subpopulation of DKFZ-EP1NS cells. Remarkably, the 5caC enrichment does not correlate with 5hmC levels and is not associated with alterations in Thymine DNA Glycosylase (TDG) expression in SHH medulloblastoma and ependymoma cell lines, but corresponds to elevated levels of TET1 transcript in UW228-3 and DKFZ-EP1NS cells. Conclusions We demonstrate that both 5caC enrichment and elevated TET1 expression are observed in SHH medulloblastomas and ependymomas. Our results suggest that increased Tet-dependent 5mC oxidation may represent one of the epigenetic signatures of cancers with neural stem cell origin and, thus, may contribute to development of novel approaches for diagnosis and therapy of the brain tumours.